Peningkatan Pengetahuan Serta Keterampilan Penulangan dan Pengecoran Pada Masyarakat Candi Kuning, Tabanan, Bali - Surya Herlambang, Fajar; Purnawirati, I.G.A. Neny; Ardika, I Nyoman; Intara, I Wayan; Suasira, Wayan; Jaya, I Made (Mitra Akademia: Jurnal Pengabdian Masyarakat, 2023)
Reinforced concrete is the most widely used structure compared to steel or wood. Reinforced concrete is generally very easy to work with. The material is very easy to get. It's so easy, it's often done by workers who don't have knowledge and skills about concrete structures. This condition is exacerbated by building owners who do not pay attention to the details of reinforced concrete structures. The owner does not want to pay for the planning consultant or supervisor. The combination of these causes the condition of the building to be not in a safe condition even though in reality there are still many buildings that are being worked on haphazardly and are still in good condition. In the rules of Civil Engineering where safety is the main thing, the conditions above must be corrected. One of the efforts of the academic community to improve this situation is to implement a Community Service Program (PKM) in the form of Technical Guidance (Bimtek) for construction workers. This Bimtek is filled with the provision of theory and practice. The theory presented is knowledge about reinforcement and concrete constituent materials. While the practice consists of working on reinforcement: cutting, bending and assembling reinforcement. For concrete practice consists of mixing and casting concrete. From this Bimtek, the construction workers understand and able to do reinforcement, mix and pour concrete properly. It is hoped that after attending this Bimtek, the construction workers will be able to apply their knowledge and skills to the projects they are working on in order to obtain a good reinforced concrete structure. In its implementation, this Bimtek received a good reception from the Perbekel and the community. In his speech, the Perbekel of Candi Kuning Village hoped that the masons who had attended this Bimtek would become pioneers of correct concrete structure work, be able to increase competitiveness and get increased wages. Through the representatives of the participants, they expressed their gratitude for the knowledge taught and hoped that similar activities could be carried out again.